2012
DOI: 10.1016/j.jvs.2011.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Peripherally inserted central catheter usage patterns and associated symptomatic upper extremity venous thrombosis

Abstract: The incidence of symptomatic PICC-associated UE DVT is low, but given the number of PICCs placed each year, they account for up to 35% of all diagnosed UE DVTs. Larger-diameter PICCs and malignancy increase the risk for DVT, and further studies are needed to evaluate the optimal vein of first choice for PICC insertion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
105
3
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(118 citation statements)
references
References 22 publications
4
105
3
6
Order By: Relevance
“…Studies showed a range of 42 to 82.4% of PICC insertions in the right side of the body (10)(11) . There is similarity in veins of the upper limb on both right and left side from the hands through to the subclavian veins.…”
Section: Resultsmentioning
confidence: 99%
“…Studies showed a range of 42 to 82.4% of PICC insertions in the right side of the body (10)(11) . There is similarity in veins of the upper limb on both right and left side from the hands through to the subclavian veins.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers noted PICC lines inserted into the basilic vein were associated with higher incidence (3.1%) of VTE than those that are inserted into the cephalic or brachial veins. 14 Location of the catheter insertion has been noted as a predisposing factor to the development of VTE. In a retrospective review of 400 cases, those with left-sided catheter insertion were noted to be more likely to develop a VTE.…”
Section: Venous Thromboembolism (Vte)mentioning
confidence: 99%
“…12,13 In addition to the risk of CLABSI associated with PICC lines, upper extremity venous thromboembolism (VTE) is another potential complication. 14,15 One study found 5% of hospitalized patients develop a symptomatic upper extremity VTE post PICC line insertion. 16 VTEs related to PICC lines present a challenge in clinical practice as it may interrupt and/or delay the patient's medical treatment plan.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased use of peripherally inserted central catheters (PICCs) is associated with an elevated risk of UEDVT, particularly in critically ill patients and those with malignancy or receiving chemotherapy [1,4,[9][10][11][12]. The occurrence of symptomatic PICC-associated UEDVT is small, but due to the large number of PICCs placed each year, they account for up to 35% of all diagnosed UEDVTs [13]. Roughly 1% to 7% of hospitalized patients who undergo PICC placement will develop venous thrombosis; and, the majority of these events will occur after the 14 th day post placement [10,[14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%